Les conditions feminines et la sensualite a travers des oeuvres de Emile Zola Et. G. Flaubert (Zola, Flaubert romanlarındaki kadın teması) - Biçkici, Seda (My University, 2005)
WOMAN THEME IN ZOLA AND FLAUBERT’S NOVELS Gustave Flaubert, who lived between the years 1821-1880, is one of the most important writers of French literature.Madame Bovary; the writer’s masterpiece;is a novel of a doctor’s wife who is seaching for love.This masterpiece, which was criticized by moralists when it first appeared later became one of the most successful romances.There is no other a novel that aroused such interest like Madame Bovary.Madame Bovary is a novel that , more than a century later, still arouses interest.This novel, written by Flaubert at the age of thirty-five, is the writer’s fist novel. Flaubert maintained his formal and intellectual search after writing Madame Bovary.He wrote several novels such as “ Salambo, Sentimental Education, Three Stories”. When Madame Bovary first appeared, Flaubert even in that century, was judged because of its supposed violation of moral and religious values.The prosecutor Pinard, who is well-known even today, claimed that the main goal of the novel was the exaggeration and incitement of sexual instincts.He suggested that unfaithfulness was praised and the novel created doubts in reader’s minds concerning their religious beliefs.The novelist was found not guilty at the end of the trial.Madame Bovary, though many years have passed, is considered to be the greatest novel French literature. Madame Bovary is a story of a woman who is searching for romantic dreams.Emma Bovary is a beautiful peasant girl.She gets married to a doctor and starts to led an ordinary life.She is helpness to supress her desire to love and to be loved in return and her unsatisfied passious.For this reason, she takes tremendous risks and experiences bitter frustrations.She loves but she isn’t loved.She sacrifices her most precious and sacred things but she is betrayed in return.That burning passion in herself leds her to a more terrible end.Madame Bovary is an excellent novel that depicts the agonies of a woman’s soul in an effective way. Flaubert was influenced by the real life story of Evogene Delamart died in great sorrow due to his wife’s unfaithfulness and by a handwritten book ‘The Memories of Madame Lodavica. Flaubert managed both to attract and repulse the readers of the nineteenth century as far as theme of the novel and his objectivity are concerned. The novel was completed in five years and serialised in Revue magazine in 1856.It depicts the life of the bourgeoise in a very realistic way Flaubert, while working on Madame Bovary,says: ‘My poor Bovary is now suffering and crying in more than twenty villages in France. Education Sentimentale presents a panorama of France of 1848 Revolution period.A splendid masterpiece…A love affair between a young man and an eldery married woman is narrated with the characters’ dilemmas, hopes, mistakes and lies. Zola wrote for Evenement, Figaro, Tribune, Gaulous,Rappel and la Cloche after 1870.He mentioned his admiration for Balzac, Flaubert and Goncourt in many of his surveys.He struggled to improve literature and he wanted the truth to be represented in an intensive and realistic way.His greatest achievement lies in the creation of his characters.Having influenced by Taine he tried to show the world and the people exactly as they were. After his first unsuccesful attempts, he attracted attention with his novel Theresa Raquin. Especially in his novels, by exploring unspoken pleasures, secret desires and hidden crimes, he created “naturalism”.In all his works, he depicted the struggle of the human soul with unforgettable scenes.He favoured Manet and the artists of Batignolles School who were later given the name of “impressionists”. Germinal; Emile Zola , who is acknowledged as the greatest author of the naturalist literature, lived between the years 1840-1902.Zola who defended the insignificance of man and the importance of nature and the environnement, tried to prove this point of view in all his works.He depicted the mass movements and the psychological states of the mass with innumerable characters.Germinal, which he wrote in1885, deals with the miners’ difficult life. Assomoir; At the time of its first publication, it attracted outraged reviews from some French novelists but some novelists were on Zola’s side. In that year the book was published thirty eight times.The book became popular owing to the reader’s common sense.The point that the critics focused on was that Emile Zola had chosen the workers life as the theme of a novel.The people who were against the novel are now forgotten but Assommoir became one of the best of Zola’s novels.This novel later caused “American Proletariat movement” to emerge.Emile Zola says ‘ In fact I am not defending myself.The novel I have written is going to defend me.I have written a novel that shows the realities as they are.The characters are not bad but illiterate.They are the people worn out by poverty. Nana; Emile Zola was aware of the reality that every person sells something in the capitalist world even in the early days of capitalism.Women who do not have anything to sell, sell their bodies and men sell their honour. Nana was created and became a novel based on Zola’s socialist ideas.It is an excellent story of money and its tricks, in other words human’s isolation.Nana, by these qualities, become the novel of the people under the influence of Marxism. According to Marxism, the changes in history are the result of a struggle between social classes and the world we live in should be changed into a now world where people live in prosperity.Nana possesses the social theme that makes this change necessary.Emile Zola wrote twenty successive novels and with them he depicted a family’s natural and social history.Nana is the greatest of all. Nana is a story of a prostitute.In the first part of the novel, we witness Nana’s success as an actress and in the second part Zola depicts her failure as a prostitute.No sooner had the novel appeared than it aroused great interest among the readers and the critics.Nana is not only a successful prostitute but also a symbol of superhuman sexuality.Nana, as being real and myth, a prostitute but also a symbol of superhuman sexuality is the most myhtical example of prostitution in literature. For Nana,EmileZola says: In this novel, Zola depicts a woman’s, a regime’s and a society’s failure and corruption.In that depiction, sexuality, history and myth are together and eventually doomed to collapse.
Keywords: Fransız Edebiyatı